Macroprudential Policy and Labor Market Dynamics in Latin America - Alan Finkelstein Shapiro; Andrés González Gomez (Inter-American Development Bank (IDB), 2015)
This paper builds a small open economy business cycle model with labor and financial market frictions that incorporates frictional, endogenous self-employment entry and a link between formal credit markets, informal credit, and the labor market. The paper then shows that the model is consistent with the cyclical behavior of both labor and credit markets in Latin American economies and analyzes the aggregate consequences of cyclical macroprudential policy for labor market and aggregate dynamics. It is found that a policy that reduces credit fluctuations successfully reduces consumption, investment, and output volatility, but generates substantially higher unemployment fluctuations in response to productivity shocks. Moreover, the policy increases the volatility of all these variables in response to net worth shocks. The link between formal credit markets, input credit between firms, and self-employment plays a key role in explaining the adverse impact of macroprudential policy on unemployment dynamics. The findings point to potential gains from policy complementarities between macroprudential regulation and active labor market interventions over the business cycle.
hdl:11319/6866
Keywords: E24; E32; G18; O17; 330; Business cycles; Labor search; Macroprudential policies; Financial frictions